Impedance-Based SHM with High Frequency Excitation Signals of Variable Amplitude and Duration - Budoya, Danilo [UNESP]; Campeiro, Leandro [UNESP]; Baptista, Fabricio [UNESP] (Springer Nature, 2023)
Measuring the electrical impedance of piezoelectric transducers is an important step in structural health monitoring (SHM) systems with damage detection based on the electromechanical impedance (EMI) technique. Studies reported in the literature usually analyze the performance of commercial and alternative measurement systems at low frequency. However, the excitation of the transducer with a high frequency, typically above 1 MHz, allows the detection of incipient damage, making it necessary to analyze measurement systems at high frequencies. As it is an analysis region still little explored for the EMI technique, it is necessary to analyze the repeatability of measurements, since the variation of the structural condition is given by the application of damage indices that quantify the differences between impedance signatures obtained before and after the damage incidence. Therefore, experimental tests were carried out using a piezoelectric diaphragm coupled to an aluminum structure, in order to verify the accuracy of measurements by varying the duration and amplitude of the excitation signals of a measurement system that uses sinusoidal signals. The results indicate that the variation of these parameters directly interferes with the precision of the measurements and the impedance signatures, enabling more reliable analyzes to be obtained about the structural condition.
Keywords: Amplitude; Duration; Electromechanical Impedance (EMI); Excitation signal; Piezoelectric diaphragm